Cryptosporidium spp surveillance and epidemiology in Ireland: a longitudinal cohort study employing duplex real-time PCR based speciation of clinical cases. Issue 11 (14th May 2020) - O'Leary, Jennifer K; Blake, Liam; Corcoran, Dan; Elwin, Kristin; Chalmers, Rachel; Lucey, Brigid; Sleator, Roy D
Abstract : Cryptosporidium is a leading cause of gastroenteritis (cryptosporidiosis), with significant morbidity and mortality worldwide. Irish cryptosporidiosis incidence rates are consistently the highest reported in Europe. A retrospective, longitudinal study of clinical Cryptosporidium isolates was conducted from 2015 to 2018 in Cork, southern Ireland. Overall, 86.5% of cases were attributed to C. parvum, while the remaining 13.5% were caused by C. hominis . Despite the widespread implications of this protozoan parasite in sporadic and outbreak-related illness in Ireland, the current dearth of species-level epidemiological surveillance and clinical studies needs to be addressed in order to elucidate the national impact of this enteric pathogen.